Parallel comparison of T cell and B cell subpopulations of adenoid hypertrophy and tonsil hypertrophy of children - Zihui Yu; Ziying Xu; Tongtong Fu; Shiyu Liu; Jinghua Cui; Bing Zhang; Jieqiong Liang; Chong Pang; Yuehua Ke; Ruikun Wang; Zhijie Tang; Yagang Gao; et al. (Nature Communications)
Abstract The adenoids and tonsils are important immune organs of the nasopharynx that often become hypertrophic in childhood because of recurrent pathogen infection. However, the differences in the immune microenvironment of adenoid hypertrophy (AH) and tonsil hypertrophy (TH) are unclear. Here, we show the epidemiological characteristics and peripheral blood cell indices of 1209 pediatric patients (1–15 years old) diagnosed with AH, and find that AH is often accompanied by TH and characterized by specific changes in immune cell types. Single-cell RNA sequencing analysis show that 12 paired AH and TH samples contain large numbers of B, T cells and some exhausted effector memory CD4+ T cells. Compared with matched TH, AH have more naïve B cells and regulatory CD4+ T cells and less plasma B cells. Weaker antigen presentation and more significant immunosuppression are also observed in AH. In contrast, the number and cytotoxicity of cytotoxic CD8+ T cells decrease with AH grade. These findings will help our understanding of the immune response to nasopharyngeal infection.